1988
DOI: 10.1111/j.1600-0773.1988.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy and Sex Steroids on α1‐Adrenoceptor Mechanisms in the Guinea‐Pig Uterine Vascular Bed

Abstract: Adrenoceptor mechanisms in the extrinsic uterine arteries from late pregnant guinea-pigs were characterized pharmacologically and compared with contractile responses of uterine arteries from non-pregnant and oophorectomized control, progesterone and oestrogen treated animals. Pregnancy caused an increase in diameter of the arteries, more pronounced the more distal they were. There was no change in potassium-evoked maximum contractions during pregnancy.Noradrenaline (10 nM to 1 mM), in the presence of cocaine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
4
9
1
Order By: Relevance
“…Nevertheless, experimental data from our study are very similar to those obtained with nonpregnant and pregnant human uterine radial arteries (Steele et al, 1993). In addition, the pD2 and maximal response values for non-pregnant and pregnant guinea-pig uterine artery with intact endothelium obtained from the present investigation are similar to those reported by Edvinsson (1986) andFallgren et al (1988).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, experimental data from our study are very similar to those obtained with nonpregnant and pregnant human uterine radial arteries (Steele et al, 1993). In addition, the pD2 and maximal response values for non-pregnant and pregnant guinea-pig uterine artery with intact endothelium obtained from the present investigation are similar to those reported by Edvinsson (1986) andFallgren et al (1988).…”
Section: Discussionsupporting
confidence: 81%
“…This conclusion is consistent with the concept that in nonpregnant and pregnant guinea-pig uterine arteries with intact endothelium m-adrenoceptors are mainly of the ml subtype (Fallgren & Edvinsson, 1986;Fallgren et al, 1988 (Cocks & Angus, 1983;Lues & Schumann, 1984;Aloschie & Godfraind, 1988). It has been also demonstrated that in some blood vessels removal of endothelium enhanced receptor reserve for noradrenaline (Alosachie & Godfraind, 1988).…”
Section: Discussionsupporting
confidence: 80%
“…These important changes occur in parallel with augmented responses of these vessels to some vasoconstrictors and to intraluminal pressure (12,14,35,48,59,61). The balance between augmented vasodilator and vasoconstrictor mechanisms determines uterine arterial tone and, consequently, blood flow to the placenta and fetus.…”
mentioning
confidence: 99%
“…One possibility may be alterations in signal transduction pathways [84], which may account for the reduction of pressor responses to various vasoconstrictor agonists [85,86]. The increased synthesis and release of various endothelium-dependent relaxing factors, such as NO and PGI # [87,88], a decrease in the number of adrenergic receptors and a blunting of reflex cardiac responses [89,90] have also been implicated.…”
Section: Vascular Function In Pregnancymentioning
confidence: 99%